2002
DOI: 10.1523/jneurosci.22-21-09549.2002
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Recency Judgment

Abstract: The prefrontal cortex plays a critical role in recollecting the temporal context of past events. The present study used eventrelated functional magnetic resonance imaging (fMRI) and explored the neural correlates of temporal-order retrieval during a recency judgment paradigm. In this paradigm, after study of a list of words presented sequentially, subjects were presented with two of the studied words simultaneously and were asked which of the two words was studied more recently. Two types of such retrieval tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
52
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 52 publications
17
52
0
Order By: Relevance
“…In addition, activity in right DLPFC was significantly correlated with recency accuracy, and marginally correlated with recency RT. In general, our findings of greater right DLPFC activity during retrieval events versus ordering events are consistent with studies that have found greater right PFC during EM retrieval in general (Habib, Nyberg, & Tulving, 2003;Nyberg, Cabeza, & Tulving, 1996) and during temporal context retrieval specifically (Dobbins, Rice, Wagner, & Schacter, 2003;Konishi et al, 2002;Rajah & McIntosh, 2006;Suzuki et al, 2002). However, due to the relatively short delay (30 sec) between encoding and retrieval in the current study design, it may be argued that the retrieval tasks employed in this study reflected retrieval from WM and not from EM.…”
Section: Retrieval-related Activity In Right Dlpfcsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, activity in right DLPFC was significantly correlated with recency accuracy, and marginally correlated with recency RT. In general, our findings of greater right DLPFC activity during retrieval events versus ordering events are consistent with studies that have found greater right PFC during EM retrieval in general (Habib, Nyberg, & Tulving, 2003;Nyberg, Cabeza, & Tulving, 1996) and during temporal context retrieval specifically (Dobbins, Rice, Wagner, & Schacter, 2003;Konishi et al, 2002;Rajah & McIntosh, 2006;Suzuki et al, 2002). However, due to the relatively short delay (30 sec) between encoding and retrieval in the current study design, it may be argued that the retrieval tasks employed in this study reflected retrieval from WM and not from EM.…”
Section: Retrieval-related Activity In Right Dlpfcsupporting
confidence: 91%
“…Neuroimaging studies have highlighted the role of various PFC regions during temporal context retrieval (Cabeza, Anderson, Houle, Mangels, & Nyberg, 2000;Dobbins, Rice, Wagner, & Schacter, 2003;Dudukovic & Wagner, 2007;Konishi et al, 2002;Suzuki et al, 2002). However, it remains unclear which of these PFC activations are related to mediating domain or task-specific cognitive control processes such as, recollection-based retrieval monitoring, familiarity-based retrieval monitoring, retrieval success and establishing retrieval mode (Dobbins, Rice, Wagner, & Schacter, 2003;Nyberg et al, 1995;Yonelinas, Otten, Shaw, & Rugg, 2005) and which are related to mediating domaingeneral cognitive control processes including strategic ordering and controlled selection processes, to name a few (Moscovitch, 2002;Rajah & McIntosh, 2006;Rowe, Toni, Josephs, Frackowiak, & Passingham, 2000;Schumacher, Elston, & D'Esposito, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the posterior part of the inferior frontal sulcus is implicated in inhibitory control during set shifting͞task switching (13,14,(16)(17)(18)(19)39) and during other inhibitory situations such as the go͞no-go (32-36), Stroop (40), and controlled retrieval tasks (41)(42)(43)(44). The region of interest analysis in the present work also showed that, besides the left anterior prefrontal region, the release trials also involved the posterior inferior prefrontal region.…”
Section: Discussionsupporting
confidence: 74%
“…The number of segments across all clips ranged between 4 and 10. The first and last segments were always excluded for the retrieval tests to mitigate end‐of‐list distinctiveness effects [Cabeza et al, 1997; Konishi et al, 2002]. Specifically for Exp 2, we divided each clip into 20 segments with equal duration.…”
Section: Methodsmentioning
confidence: 99%